A revised (earliest Vallesian) age for the hominoid-bearing locality of Can Mata 1 based on new magnetostratigraphic and biostratigraphic data from Abocador de Can Mata (Vallès-Penedès Basin, NE Iberian Peninsula). Issue 170 (September 2022) - Alba, David M.; Robles, Josep M.; Casanovas-Vilar, Isaac; Beamud, Elisabet; Bernor, Raymond L.; Cirilli, Omar; DeMiguel, Daniel; Galindo, Jordi; Llopart, Itziar; Pons-Monjo, Guillem; Sánchez, Israel M.; Vinuesa, Víctor; et al.
Abstract: The Abocador de Can Mata (ACM) composite stratigraphic sequence (els Hostalets de Pierola, Vallès-Penedès Basin, NE Iberian Peninsula) has yielded a diverse primate assemblage from the late Aragonian (Middle to Late Miocene). Detailed litho-, bio-, and magnetostratigraphic control has enabled an accurate dating of these fossil remains. Comparable data, however, were lacking for the nearby locality of Can Mata 1 (CM1), which yielded a dryopithecine canine of a female individual. Given the lack of hipparionin equids and giraffids, CM1 has been correlated to the latest Aragonian (Mammal Neogene [MN] zone MN7+8). Here we revise the age of CM1 based on fieldwork and associated paleomagnetic samplings undertaken in 2018–2021. Our results extend the ACM composite sequence upward and indicate that CM1 correlates to the earliest Vallesian (MN9). The updated ACM sequence has a thickness of ∼300 m and comprises 12 magnetozones correlated to subchrons C5Ar.1r to C5n.2n (∼12.6–11.1 Ma; latest MN6 to earliest MN9, late Aragonian to earliest Vallesian). CM1 is correlated to C5r.1r (11.146–11.056 Ma), with an interpolated age of 11.11 Ma, thus postdating the dispersal of hipparionin horses into the Vallès-Penedès Basin—which is correlated to the previous subchron C5r.1n, with an interpolated age of 11.18 Ma, and by definition marks the beginning of the Vallesian. CM1 also minimally postdates the earliest record of giraffids at ACM—representing their earliest well-dated occurrence in the basin—being correlated to C5r.1n with an interpolated age of 11.11 Ma. We conclude that CM1 has an earliest Vallesian (MN9) age of ∼11.1 Ma, intermediate between the Aragonian dryopithecins and the Vallesian hispanopithecins. Ongoing paleontological surveillance at ACM thus offers the prospect to yield additional earliest Vallesian ape remains, which are essential to clarify their taxonomic allocation as well as to confirm whether hispanopithecins evolved locally from dryopithecins rather than immigrating from elsewhere during MN9.